2015
DOI: 10.1016/j.redox.2014.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive effect of mitochondria-targeted proxyl nitroxides

Abstract: Superoxide (O2-•) has been implicated in the pathogenesis of many human diseases including hypertension. Mitochondria-targeted superoxide scavenger mitoTEMPO reduces blood pressure; however, the structure–functional relationships in antihypertensive effect of mitochondria-targeted nitroxides remain unclear. The nitroxides are known to undergo bioreduction into hydroxylamine derivatives which reacts with O2-• with much lower rate. The nitroxides of pyrrolidine series (proxyls) are much more resistant to bioredu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…We have previously shown that mitochondria-targeted superoxide dismutase mimetic mitoTEMPO reduces mitochondrial superoxide in endothelial cells treated with hormone angiotensin II or H 2 O 2 while untargeted analogue TEMPOL was not effective [10,19]. In this work, we have compared the antioxidant effect of mitoTEMPO and DCP-AM2 on mitochondrial superoxide level.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…We have previously shown that mitochondria-targeted superoxide dismutase mimetic mitoTEMPO reduces mitochondrial superoxide in endothelial cells treated with hormone angiotensin II or H 2 O 2 while untargeted analogue TEMPOL was not effective [10,19]. In this work, we have compared the antioxidant effect of mitoTEMPO and DCP-AM2 on mitochondrial superoxide level.…”
Section: Resultsmentioning
confidence: 97%
“…In contrast, incubation of endothelial cells with DCP did not lead to significant consumption of DCP nitroxide from the buffer and only minor accumulation of DCP in cells was observed (Figure 2). Interestingly, incubation of cells with mitoTEMPO lead to significant absorption of nitroxide from the buffer; however, no significant EPR signal of mitoTEMPO in cells was found due to rapid cellular bioreduction [10]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many researchers have reported that stable nitroxide radicals are appropriate redox sensors for ROS imaging and undergo bioreduction to hydroxylamine derivatives, which can react with superoxide (85)(86)(87). For example, nitroxides as mito-TEMPO and mito-carboxy-PROXYL are mitochondria-targeted derivatives of TEMPOL and carboxy-PROXYL, which currently are widely used as redox-sensors for detection of abnormal superoxide generation in living cells and tissues (2,28,37,(88)(89)(90)(91).…”
Section: Nitroxides As Redox Sensors For Detection Of Mitochondrial Dmentioning
confidence: 99%